GAMBARAN SARANA PROTEKSI KEBAKARAN AKTIF DAN PASIF DI PT. PLN (PERSERO) PENYALURAN DAN PUSAT PENGATUR BEBAN (P3B) SUMATERA, UNIT PELAKSANA TRANSMISI (UPT) PADANG 2019 - Friska Eka Fitria (Ensiklopedia of Journal, 2020)
PT. PLN (Persero) P3B Sumatra, UPT Padang, had a small fire caused by cables that were not in accordance with SNI. At the time of the fire the smoke detector does not function and therefore it is necessary to ensure that all fire protection facilities are in good condition so that it can be functioned in the event of a fire. PT. PLN (Persero) P3B Sumatra, UPT Padang has good active and passive fire protection facilities and is visible in the APAR laying office area which is close together, alarms that still use manual alarms, there are emergency stairs, evacuation routes and collection points. The purpose of this study was to determine the description of active and passive fire protection facilities at PT. PLN (Persero) P3B Sumatra, UPT Padang. The design of this study is descriptive in that it looks at an overview of active and passive fire protection facilities at PT. PLN (Persero) P3B Sumatra, UPT Padang. This research was conducted at PT. PLN (Persero) P3B Sumatera, UPT Padang, which is located at Jln, Bypass km 6 Lubuk Begalung, South Padang and held in March-September 2019. The object of this research is 6 units. The technique of collecting data was observation by using a checklist and interview. The results of this study show that fire alarms are 60% (enough), fire detectors 0% (not suitable), fire extinguishers 85% (good), emergency exits 56% (less), evacuation direction instructions 100% (good) and gathering points 67% (enough). It is expected that for companies to use automatic alarms rather than manuals so that it is easy and quick to evacuate when an emergency occurs, an inspection of the fire extinguisher must be carried out periodically whether it is the condition or equipment of the fire extinguisher and the physical condition of the fire extinguisher.